Structural and Physicochemical Tuning of Binary and Ternary Mn-Based Layered Double Hydroxides via Alkali-Free Synthesis for Advanced Material Applications (Indonesian Journal of Science and Technology, 2026)
This study explores the alkali-free synthesis of binary (MnCo) and ternary (MnCoCr) layered double hydroxides (LDHs) to enhance structural and physicochemical properties relevant to advanced catalytic systems. The materials were synthesized using an ammonium nitrate buffer, followed by controlled ageing and calcination. Characterization included PXRD, BET, TGA, FESEM, and FTIR techniques. The ternary MnCoCr LDH demonstrated improved crystallinity, larger surface area, and more uniform morphology compared to the binary MnCo LDH. These enhancements occurred because chromium altered interlayer spacing and cation interactions, promoting better nucleation and structural integrity. The findings suggest that careful control of metal composition and synthesis conditions can effectively tailor LDH properties. This approach supports sustainable materials engineering and opens new possibilities in catalysis, adsorption, and energy storage applications.
Keywords: Alkali-free; Layered double hydroxide; Physiochemical; Secondary; Tertiary